Systematic Review: The Effectiveness of Non-Pharmacological Interventions in the Management of Knee Osteoarthritis - Muh Gufron; Andi Dhedie Prasatia Sam; Syarif Hidayatullah (Journal La Medihealtico, 2026)
Knee osteoarthritis is a chronic degenerative disease that often causes pain, joint dysfunction, and reduced quality of life, especially in the elderly. Non-pharmacological therapy is recommended as the primary approach in the management of knee osteoarthritis because it is safe and sustainable. This study aims to examine the effectiveness of various non-pharmacological interventions in the management of knee osteoarthritis through a qualitative systematic review method. Literature searches were conducted in the PubMed, Scopus, SINTA, and Google Scholar databases with a publication range of 2020–2026, using keywords related to knee osteoarthritis and non-pharmacological interventions. The articles included were experimental studies and clinical trials involving knee osteoarthritis patients and reporting clinical outcomes such as pain, joint function, and quality of life. The results of the review showed that non-pharmacological interventions, including physical exercise, patient education, weight management, physiotherapy, and complementary therapies such as Tai Chi and acupuncture, were consistently effective in reducing pain, improving joint function, balance, and quality of life in patients. Therefore, non-pharmacological therapies can be recommended as first-line therapy or long-term supportive therapy in the management of knee osteoarthritis.